Analisis Keterampilan Berpikir Kritis Siswa di Sekolah Menengah Kejuruan (SMK) Menggunakan Metode Ekspositori dalam mata Pelajaran Sanitasi, Hygiene, dan Keselamatan Kerja (SHKK) - Sukriyadi, Sukriyadi; Burhanuddin, Burhanuddin; Mustofa, Hisbulloh Als; Bilad, Muhammad Roil (Lensa: Jurnal Kependidikan Fisika, 2025)
This study aims to analyze the critical thinking skills of vocational high school (SMK) students and to identify the factors influencing their development within the context of expository teaching in the subject of Sanitation, Hygiene, and Work Safety (SHWS). The research employed a one-shot case study design using both quantitative and qualitative approaches. A total of 20 tenth-grade students from a public vocational high school in Central Lombok were selected as research participants. Quantitative data were collected through open-ended tests designed to measure critical thinking skills across five key indicators, while qualitative data were obtained from open-ended interviews with subject teachers. The results showed that students' critical thinking skills fell into the "moderately critical" category, with an average score of 2.380 on a 5-point scale. The data also revealed significant variation among students, with no participants achieving the “critical” or “highly critical” categories. Thematic analysis of teacher interviews identified four main factors affecting the development of critical thinking: student learning readiness, the effectiveness of the expository method, limited practical facilities, and structural challenges in instructional implementation. The study concludes that the expository method is not fully effective in fostering students’ critical thinking skills, particularly in practice-based subjects such as SHWS. These findings highlight the importance of implementing more participatory and contextual learning strategies, improving access to practical resources, and strengthening teacher capacity in critical thinking pedagogy to produce vocational graduates who are cognitively competent and adaptive.